1979
DOI: 10.1037/0022-0167.26.5.427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of systematic physical fitness training combined with counseling on the self-concept of college students.

Abstract: Three groups of 40 college students were each given different treatments in an experiment designed to investigate the effect of systematic physical fitness training combined with counseling on measured self-concept. One experimental group received a fitness program consisting of flexibility training and systematic distance running; a second experimental group received the same physical training plus 1 hour per week of group counseling designed to reinforce progress made in the fitness program; and a third grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
1

Year Published

1980
1980
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 18 publications
1
36
0
1
Order By: Relevance
“…Thus, it is unclear whether the observed effect was due to the training program or to preexisting group differences (17). Nevertheless, these results are consistent with numerous reports suggesting that aerobic training enhances self-mastery (16,29,30). Finally, no relationship was observed between improvement in aerobic fitness and subjective measures of arousal or anxiety during the session, self-reported frequency or intensity of daily hassles and uplifts, or psychologic symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, it is unclear whether the observed effect was due to the training program or to preexisting group differences (17). Nevertheless, these results are consistent with numerous reports suggesting that aerobic training enhances self-mastery (16,29,30). Finally, no relationship was observed between improvement in aerobic fitness and subjective measures of arousal or anxiety during the session, self-reported frequency or intensity of daily hassles and uplifts, or psychologic symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, a third series of studies have reported positive psychological changes accompanying physical exercise in specialized populations such as children (15), collge students (16), cardiac patients (17), or psychiatric patients (18,19).…”
mentioning
confidence: 99%
“…Employees who are not coping effectively generally lack self-efficacy regarding their abihty to cope, and experience a desire for greater personal control (Lazarus and Folkman 1984). Hilyer and Mitchell (1979) found that participants who experienced positive changes in self-concept through a fitness training and counselling treatment had low self-concepts to begin with. They suggested that individuals with high self-concepts did not need to change as much.…”
Section: Psychological Criteriamentioning
confidence: 98%